Software fault tolerance techniques and implementation - Pullum, Laura L. (Artech House computing library., 2001)
Look to this innovative resource for the most comprehensive coverage of software fault tolerance techniques available in a single volume. It offers you a thorough understanding of the operation of critical software fault tolerance techniques and guides you through their design, operation and performance. You get an in-depth discussion on the advantages and disadvantages of specific techniques, so you can decide which ones are best suited for your work. The book examines key programming techniques such as assertions, checkpointing, and atomic actions, and provides design tips and models to assist in the development of critical fault tolerant software that helps ensure dependable performance. From software reliability, recovery, and redundancy ... to design and data diverse software fault tolerance techniques, this practical reference provides detailed insight into techniques that can improve the overall dependability of your software.